2017
DOI: 10.1063/1.5006396
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of elastic anomalies in niobium at high pressure and temperature

Abstract: Niobium does not show any structure transition up to very high pressures. Nonetheless, by using density functional theory, we demonstrate in this work that it exhibits striking softening in elastic moduli C44 and C' at a pressure from 20 to 150 GPa. A novel anomaly softening in C44 from 275 to 400 GPa is also predicted. The physics behind these two anomalies is elaborated by electronic structure calculations, which revealed that they are actually different, with the first one directly relates to an underlying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
0
13
0
4
Order By: Relevance
“…Wang et al [92] have concluded that this anomalous behavior of the Nb shear modulus C 44 in the pressure range 0-600 kbar mainly comes from the underlying Rh1 and Rh2 distortion and has the same softening mechanism which is observed in vanadium. According to Jing et al [88], a similar hypothesis can be also applied to the softening of the shear modulus in tantalum.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Wang et al [92] have concluded that this anomalous behavior of the Nb shear modulus C 44 in the pressure range 0-600 kbar mainly comes from the underlying Rh1 and Rh2 distortion and has the same softening mechanism which is observed in vanadium. According to Jing et al [88], a similar hypothesis can be also applied to the softening of the shear modulus in tantalum.…”
Section: Discussionmentioning
confidence: 86%
“…As was mentioned above, Struzhkin et al [40] have observed anomalies in the superconducting transition temperature T c in Nb at 50-60 kbar and suggested that this anomaly arises from the ETT. Wang et al [92] have also suggested that the ETT could be responsible for the unusual behavior of the compressive strength around 50-60 kbar.…”
Section: Strength and Elasticity Of Nb And Tamentioning
confidence: 99%
See 2 more Smart Citations
“…Landa et al [5,6] and Koči et al [7] predicted a shear elastic softening of Nb from 20 to 150 GPa based on 0 K density functional theory (DFT) calculations. Based on the assumption that the thermal excitation of the electrons is the most significant temperature effect, Wang et al [8] performed static DFT calculations, varying the electronic temperature and including the thermoelectronic entropy to predict the temperature dependence of the C 44 shear elastic constant. The occurrence of the shear elastic softening has been suggested up to 2000 K. However, an absence of any phonon contribution which is expected to be significant at high temperatures calls for a reconsideration of this conclusion.…”
mentioning
confidence: 99%